Stability and effectiveness of cocoa husk liquid smoke in varied storage times as a control agent for Phytophthora palmivora infection - Alia, Nur’; Ursam, Andreas Hananto Pratomo; Fitriani, Mita; Juniantari, Desak Made; Tiara, Tiara; Tenriawaru, Eka Pratiwi (Biogenesis: Jurnal Ilmiah Biologi, 2026)
Pod rot disease, caused by Phytophthora palmivora, is a major factor contributing to the decline in cocoa productivity. The growth of this fungus can be inhibited by using liquid smoke from cocoa husks. However, the stability and effectiveness of cocoa husk liquid smoke at different storage times have not been studied, even though these parameters are critical for its potential use as a fungicide. The purpose of this study was to test the stability and effectiveness of cocoa husk liquid smoke, at various storage time, against P. palmivora. Cocoa husk liquid smoke was obtained from the pyrolysis of cocoa husks at a temperature of 500 °C. The treatments consisted of storage times of 1 day, 3 days, 6 days, and 9 days. The test consisted of a stability test, in vitro test, and in vivo test. Sterile distilled water was used as a negative control and chemical fungicides (antracol) as a positive control. Data were analyzed using analysis of variance with a significant level of 5% and continued with Tukey’s further test. The results showed that cocoa husk liquid smoke remained chemically stable up to 6 days of storage based on color, aroma, and pH and meet the SNI 8985:2021 quality criteria 2. The results of the in vitro test showed that storage times of up to 9 days still showed inhibitory ability against P. palmivora, while the results of the in vivo test showed the best performance at storage times of 6 days. The active compounds in cocoa husks liquid smoke at storage 6 days show the fenol and organic acid which able to inhibit the fungus growth.